Investigação da usinabilidade das ligas de alumínio da série 6xxx - Gonçalves, Ricardo Augusto (2012)
Due the wide use of the aluminum alloys and their large participation in the market, the producers need more knowledge about the alloys behavior in manufacturing process to provide more technical data for his clients. In this scenario the machining is one of the most use processes in the industry. This work has as the main purpose to investigate the machinability in turning of five aluminum-magnesium-silicon alloys of the 6XXX series (6082, 6351, 6005A, 6063 and 6061) in terms of the three components of machining force, surface roughness, chip thickness ratio and chip shape using carbide tools of the N class. Following a statistic planning it was check the effect of cutting parameters: cutting speed, feed rate and depth of cut. The results showed that usually the cutting forces in machining 6082 alloy were higher. In terms of roughness, the best results were achieved with 6063 alloy, which also had higher chip thickness ratio. The chips formed in machining of the alloys usually had the short helical and loose arc forms. This research showed the differences when machining the five alloys generating important data for manufacturers and industry that uses this aluminum alloys.